(untitled) (The Research of Medical Science Review, 2025)
This research investigated the nutritional properties of mulberry jam. Mulberry jam is rich in bioactive compounds, including flavonoids, vitamins, and minerals Its potential application as a functional food has gained attention due to its high nutritional value. The study involved preparing mulberry jam and analyzing its composition (crude protein, fiber, ash, moisture), total sugars, minerals, and vitamin C over one month, with assessments at 0, 15, and 30 days. Most parameters showed non-significant effects. Proximate analysis revealed the following mean values for the control treatment (100% pulp): moisture content at 27.43%, crude protein at 0.23%, crude fat at 0.26%, and crude fiber at 0.67%, indicating a low-fat, high-energy jam suitable for health-conscious consumers. Throughout the storage period, total soluble solids (TSS) were recorded at 57.67 initially and increased to 58.26 by the end, while total and reducing sugars demonstrated an upward trend. Vitamin C levels experienced a significant decline, highlighting the critical need for improved storage methods to mitigate nutrient loss. Sensory evaluation showed consistent overall acceptability scores, with the control treatment maintaining an average score of 8.17 over the 30 days. Despite slight decreases in total phenolic content and antioxidant activity, results support the viability of mulberry jam as a nutritious addition to daily diets. The study suggests that mulberry jam may serve as a nutritious addition to a healthy diet and provides valuable insights for food manufacturers, nutritionists, and healthcare professionals seeking to develop and promote mulberry jam for their nutritional and health benefits.